Prototype of Smart Lock Based on Internet Of Things (IOT) With ESP8266 - Firza Fadlullah Asman; Endi Permata; Mohammad Fatkhurrokhman (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2019)
This study aims to design a prototype house that has an automatic safety system installed that has two inputs for its control. The developed system can be controlled via an Android or IOS smartphone that has the Blynk application installed, or by using a PIR sensor installed in the circuit. The output in this series of systems is solenoid lock which is used as a door lock for the house later. This research refers to the ADDIE development model with details: (1) Analyze, (2) Design, (3) Development, (4) Implementation and (5) Evaluate. Based on the testing of each component used, the results are obtained in the form of PIR sensor readings with a radius of 90cm with an angle of 120o with a voltage of 5V, a solenoid lock that uses a 12V voltage, a pin from the Wemos D1 R1 board that has errors on its 2 input / output pins, and a battery that can be used as a backup power source when the main power source goes out for more than 5 hours.